Towards collaboration between information seeking and information retrieval - Carol C. Kuhlthau (Information Research: An International Electronic Journal)
Introduction. The conceptual framework of librarianship and information science has developed rapidly over the past decade with the prospect of application in other fields. However, transfer of concepts across branches within the field remains problematic and severely limits ability to address important information problems. Requirements. A conceptual framework is needed that will integrate the diverse areas of interest. Imperatives. An integrated framework requires sustained attention to a problem area; the application of the evolving framework to the area; the development of projects that are of relevance to more than one interest group in the field; and evolving the findings of research into the implementation of systems and services. Conclusion. The challenge facing librarianship and information science today is to bring together the allied areas of the field into an overarching conceptual framework that represents the unified whole. This paper suggests a strategy to accomplish this.